2019
DOI: 10.4314/tjpr.v17i10.8
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin inhibits porcine intestinal inflammation <i>in vitro</i>

Abstract: Purpose: To investigate the effect of Quercetin (Que) on inflammatory reaction in intestinal porcine enterocyte cells, IPEC-J2, induced by lipopolysaccharide (LPS). Methods: IPEC-J2 cells were pretreated with Que and then incubated with LPS. Cell viability, cell morphology, nitric oxide (NO) content, gene expression levels of interleukin-6 (IL-6) and interleukin-8 (IL-8), were then evaluated. Results: LPS incubation at 10 μg/mL for 24 h showed no effect on the viability and cell morphology of IPEC-J2, while Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…It was reported that high concentrations of LPS between 100 and 300 µg/mL are required to reduce the viability of non-transformed rat IEC-18 enterocytes after 24 h [ 35 ]. LPS concentrations between 1 and 10 µg/mL did not affect IPEC-J2 viability until 24 h, while 10 µg/mL activated the expression of pro-inflammatory IL6 and IL8 mRNA [ 36 ]. An LPS concentration of 10 µg/mL activated pro-inflammatory genes in 8 h, although it did not cause any cytotoxic effects after 24 h [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that high concentrations of LPS between 100 and 300 µg/mL are required to reduce the viability of non-transformed rat IEC-18 enterocytes after 24 h [ 35 ]. LPS concentrations between 1 and 10 µg/mL did not affect IPEC-J2 viability until 24 h, while 10 µg/mL activated the expression of pro-inflammatory IL6 and IL8 mRNA [ 36 ]. An LPS concentration of 10 µg/mL activated pro-inflammatory genes in 8 h, although it did not cause any cytotoxic effects after 24 h [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the possible management interventions, the incorporation of plant-derived compounds into the diet appears to be a strategy to improve swine health, performance, and food-derived quality (25,26). Essential oils, from plant derivatives, are used for their antimicrobial, antioxidant, and anti-inflammatory properties (27)(28)(29)(30). Among essential oils, oregano essential oil (ORE) is used in the pig industry for its beneficial effects, ranging from improved performance to increased pork quality (31,32).…”
Section: Introductionmentioning
confidence: 99%